THE IMPACT OF CORPORATE GOVERNANCE ON DIVIDEND POLICY IN CHINA - HUANG, ZITIAN (2017)
This paper aims at examining the effect of corporate governance on dividend policy using a panel data set of total 9085 China’s listed companies over 5 years from 2012 to 2016. Based on agency theory prediction, five panel data linear regression models have been used to explore the relationships between corporate governance variables (the shareholding of the largest shareholder, ownership concentration, and dividend policy, board size, the ratio of independent director and CEO duality) dividend policy (dividend payout ratio). The empirical results show that except the ratio of independent director, corporate governance mechanism has an impact on dividend policy, but it is not the only factor.